Capital flows and economic growth in the era of financial integration and crisis: 1990 - 2010 - Joshua Aizenman; Yothin Jinjarak; Donghyun Park (University of California, Economics Department, 2011)
We investigate the relationship between economic growth and lagged international capital flows, disaggregated into FDI, portfolio investment, equity investment, and shortterm debt. We follow about 100 countries during 1990-2010 when emerging markets became more integrated into the international financial system. We look at the relationship both before and after the global crisis. Our study reveals a complex and mixed picture. The relationship between growth and lagged capital flows depends on the type of flows, economic structure, and global growth patterns. We find a large and robust relationship between FDI - both inflows and outflows - and growth. The relationship between growth and equity flows is smaller and less stable. Finally, the relationship between growth and short-term debt is nil before the crisis, and negative during the crisis.
Keywords: F43; F21; F32; 330; capital flows; economic growth; FDI; portfolio investment; equity investment; short-term debt; financial integration; financial crisis; Internationale Wirtschaftsbeziehungen; Kapitalmobilität; Direktinvestition; Portfolio-Investition; Kapitalbeteiligung; Schulden; Finanzmarktkrise; Welt